Is simple reaction time or choice reaction time an indicator of all-cause mortality or CVD mortality?. (October 2021) - Zou, T.; Cao, S.; Liu, W.; Li, L.; Jiang, J.; Wu, L.
Abstract: Objectives: Simple reaction time (SRT) and choice reaction time (CRT) have been shown to be good indicators for quantitatively assessing the level of human cognitive impairment, but these parameters have also been linked to the risk of human death. This study aimed to quantitatively assess the independent predictive value of SRT or CRT for all-cause mortality or cardiovascular disease (CVD) mortality by conducting a meta-analysis of prospective studies. Study design: The study design of this study is a prospective cohort study. Methods: We conducted a meta-analysis by combining hazard ratios (HRs) and 95% confidence intervals (95% CIs) of SRT or CRT with all-cause mortality or CVD mortality in healthy community residents aged 18 and over. Heterogeneity was evaluated by using Q statistics and Cochrane's I 2 statistics. Results: A total of seven prospective studies that examined all-cause mortality and CVD mortality were included. The pooled HR of all-cause mortality in SRT was 1.099 (1.065–1.134, I 2  = 11.9%), and an increased risk of CVD mortality was associated with lower SRT (HR = 1.186, 95% CI = 1.137–1.236; I 2  = 52.4%). Similarly, the pooled HR of all-cause mortality in CRT was 1.140 (95% CI = 1.085–1.197, I 2  = 33.7%). However, lower CRT was not statistically associated with an increased risk of CVD mortality. Conclusion: SRT may be a predictor of all-cause-mortality and CVD mortality, and CRT is significantly associated with an increased risk of all-cause mortality.